The Digital Diary: A Mobile, Multimodal, and Participatory Method and Part of Digital Ethnography - Monika Palmberger (International Journal of Qualitative Methods)
In this article I introduce the digital diary method as a multimodal, participatory qualitative approach for investigating everyday digital practices within digital ethnography. This method enables participants to document their media practices and daily activities over time by creating digital diaries that incorporate written, audiovisual, and creative elements. By encouraging the recording of multimodal data—including text, images, photos, voice recordings, and videos—the method provides rich insights into participants’ experiences and emotions. These diaries are later collaboratively reviewed and reflected on with researchers, and they offer a platform for both researchers and research partners to gain fresh insights and deeper understandings of the material discussed. The participatory nature of digital diaries highlights the agency of research partners, who maintain control over what they share and its interpretation, as illustrated through examples from my own research with refugees in Vienna on their transnational care relations. Applied selectively with key research partners, the method provided valuable insights, with participants gaining a deeper understanding of their media practices and care relationships through self-reflection. The integration of online and offline practices within these diaries demonstrates the interconnectedness of digital and lived experiences, challenging the traditional dichotomy between the two. Overall, the digital diary method not only enhances ethnographic research but also serves to explore the evolving role of digital media and its integration into broader social and cultural contexts.